Emissions of Volatile Organic Compounds (VOCs) as Safety Indicators in the Development of Wood-Based Binderless Boards - Elise Bertheau; Valérie Simon; Christine Delgado Raynaud (Applied Sciences, 2024)
Wood-based panels are ubiquitous in our daily lives, both as building materials and as furnishing materials. Numerous studies have revealed that these materials emit volatile organic compounds, such as formaldehyde, into indoor air, which can be harmful to human health. These volatile organic compounds come both from the wood itself, more specifically cellulose, hemicellulose, and lignin, and from the resins used to bind the wood fibers or particles together. Today, new panels bonded with bio-based adhesives and binderless panels are emerging. The aim of this article is to highlight the importance of measuring VOC emissions from binderless wood-based panels, and more specifically, to identify the VOCs, originating from the wood and thermal transformation processes, likely to be emitted during the production of such panels, as well as how to sample them and measure their emissions. This work provides a useful approach to identifying and quantifying VOC emissions from these new materials. These methodologies should be applied more widely to gain knowledge about VOCs, which are relevant indicators for the development of environmentally friendly materials.